The Relevance of Psychological Testing in the Selection of Army Officers - Khadka, Phatya Bahadur (Unity Journal, 2023)
Military psychological testing and assessments are vital in military life. It not only supports in training, selection, placement, and promotion purposes but also assists in the diagnosis and identification of candidates with mental problems and trauma that could pose a great risk. In 1905, the contemporary psychological testing procedure formally came into existence in France. Similarly, it adopted the test for assessing and examining soldiers during WW II for the selection of potential human resources for making war successful. After WW II, India and Pakistan began military psychological testing for the armed forces. Similarly, in the Nepali Army, the present psychological selection system and the procedure has been continuing for more than 3 decades. Therefore, a review of the present psychological system and procedure is urgent. The study used qualitative methods with the majority of the interviews emphasized on upgradation and refinement of projective technique, one-dimension approach pattern modification, improvement in rating and standardization of tests, selection of potential officer, provision of infrastructures, inadequate number of psychological experts and specialists, reactivation of Research Wing for the Psychological testing and research and lacking in posting of high-profile officers for conducting and supporting tests.